Sustained release of Lactobacillus casei cell wall extract can induce a continuous and stable IgA deposition model. Issue 3 (5th April 2022) - Wan, Feng; Wang, Hui; Wang, Manliu; Lv, Jicheng; Zhao, Minghui; Zhang, Hong
Abstract: Mucosal immune regulation is considered a key aspect of immunopathogenesis of IgA nephropathy (IgAN). Direct experimental evidence clarifying the role of intestinal mucosa attributes in IgAN is lacking. In this study, a mouse model was established via multiple low‐dose intraperitoneal injections of Lactobacillus casei cell wall extract (LCWE) emulsified with Complete Freund's Adjuvant (CFA). We found continuous and stable deposition of IgA in glomerular mesangial areas, accompanying high circulating levels of IgA and IgA–IgG complexes. Expression of the key extracellular matrix components collagen IV and fibronectin also increased in the mesangial areas of LCWE‐induced mice. IgA + B220 + B‐cell proportion increased in the small intestine (SI), Peyer's patches, inguinal lymph nodes, spleen, and bone marrow. The intestinal barrier was dysfunctional in the LCWE‐induced mice, and consistent with this, higher levels of serum zonulin (namely prehaptoglobin‐2), a regulator of epithelial and endothelial barrier function, were observed in patients with IgAN. Hematoxylin and eosin staining results indicated that immune tissues such as liver, spleen, and lymph nodes showed an inflammatory response and focal lesions. Glucocorticoid methylprednisolone treatment could alleviate serum IgA and IgA–IgG complex levels and mesangial IgA deposition. Taken together, our results indicate that we have successfully constructed a mouse model with IgA deposition in the mesangial areas of the glomeruli and provide evidence for the connection between the intestinal barrier and elevated circulating IgA and IgA–IgG in IgAN. © 2022 The Pathological Society of Great Britain and Ireland.